Proposal of a heuristic model using genetic algorithms to solve and operational port problem - Silva,Vanina Macowski Durski (2008)
This article is characterized by the presentation of some problems found in ports that emphasize the Berth Allocation Problem, for which a heuristic model has been proposed to resolve this problem. This heuristic proposal is based on Genetic Algorithms and its objective is to allow the learning of this subject, besides urging the reader to implement a computer-based tool that uses these heuristics to solve this problem, practically and efficiently.